Routledge handbook of Islamic ritual and practice - Leaman, Oliver (Routledge handbooks, 2022)
26. Sacred spaces: adaptation and early Islam / Essam Ayyad -- 27. Twelver Shiʻa Pilgrimage: Ziyara / Ingvild Flaskerud -- 28. Ziyara (ʻAlawi Ritual and Practice) / Amelia Gallagher -- 29. The Qibla: Ritual Orientation in the Formation of Islamic Collective Identity / Ari Gordon -- OTHERS: 30. Animals as Agents? A Qurʼanic / Asmaa El Maaroufi -- 31. Heresy or Moral Imperative? Islamic Perspectives on Veganism / Zinnira Shaikh -- 32. "Islamic reformism": colonial influence on Muslim intellectual practice / Mohamed Amine Brahimi -- 33. Qur'an, Rituals and Muslim Memory of Jews / Mehnaz M. Afridi -- 34. Muslim attitudes to Christian ritual and practice / Clinton Bennett -- 35. Interfaith Practices / Elizabeth Becker -- 36. Ritual, Embodiment and Creativity in the Muslim Diaspora: Transnational Migrations and Symbolic Returns / Pnina Werbner -- 37. The Secular World / Ufuk Topkara -- 38. Rituals, equality, and difference / Oliver Leaman -- Index.